Making Yogurt: A Practical Study to Develop an Understanding of Useful Bacteria - Gökşen Üçüncü; Ferhat Karakaya; Mehmet Yilmaz (Universitas Pendidikan Indonesia, 2022)
This study aims for students to comprehend the beneficial functions of bacteria with the traditional home yogurt leavening activity. Also, it aims to identify alternative concepts related to leavening and contribute to students' home yogurt consumption habits. The study is a case study. The study was conducted with 29 fifth-grade students studying at a public school in Istanbul in the 2019-2020 academic year and their parents. Questionnaire forms and student observation forms developed by the researchers were used as data collection tools. The obtained data were described by content analysis. Before the application, the participant students were given these three statements; microbes as a sample of microscopic creatures, yeast fungi caused yogurt formation, and yogurt is healthy because it was a dairy product. While after the application, participant students changed their statements to these three; the term microbe was not used as a sample of microscopic creatures, bacteria took part in the formation of yogurt, and yogurt is healthy because it contains microscopic creatures beneficial for the digestive system. The educational activities integrated into daily life contribute to students' conceptual learning.